2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27107
|View full text |Cite
|
Sign up to set email alerts
|

Unique Potential and Challenges of Students with ADHD in Engineering Programs

Abstract: A critical need exists in engineering education to draw on the non-traditional divergent thinking and risk-taking necessary for making radical technological breakthroughs. Literature suggests that individuals with Attention Deficit Hyperactivity Disorder (ADHD) characteristics demonstrate unparalleled creativity and risk-taking potential. While this group of students may offer significant benefits to the advancement of the nation, they are currently significantly underrepresented in engineering programs becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…While STEM education often resists creativity, cultivating more creatively minded students remains an important goal. Engaging and retaining neurodiverse students, including those with attention deficit hyperactivity disorder (ADHD), could contribute to a more imaginative engineering workforce capable of addressing complex, interconnected issues [7][8][9][10]. White and Shah first proposed in 2006 that ADHD increases creativity [11], a theory reinforced by their later research [12,13] and supported by additional studies [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…While STEM education often resists creativity, cultivating more creatively minded students remains an important goal. Engaging and retaining neurodiverse students, including those with attention deficit hyperactivity disorder (ADHD), could contribute to a more imaginative engineering workforce capable of addressing complex, interconnected issues [7][8][9][10]. White and Shah first proposed in 2006 that ADHD increases creativity [11], a theory reinforced by their later research [12,13] and supported by additional studies [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These numbers do not account for the number of students who do not seek accommodations, and the number of students who do not have self-knowledge about neurodiversity; previous research indicates that only 17% of students who received supports in high school seek accommodation in college [19]. Another study found that only 16.6% of participants who were formally diagnosed with ADHD were receiving services from the university's accessibility office [3]. The number of undiagnosed individuals is unknown.…”
Section: A Civil and Environmental Engineering Department As A Contex...mentioning
confidence: 99%
“…This one-size-fits-all model of teaching and learning limits opportunities not only for traditional learners to engage in interactive learning and creative problem solving but also for students whose ways of thinking fall outside of the typical range. While accommodations such as extended time on exams and assistance with notetaking may provide some form of equity for these students [3][4][5], they fail to address the underlying mismatch between the unique abilities of neurodivergent students and the demands of the traditional educational environment [3]. As it stands, the current system does very little to acknowledge the strengths of non-traditional learners [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While accommodations may help neurodivergent students succeed in higher education, many choose not to seek supports from their university's center for students with disabilities [19]. For example, one study [20] shows that fewer than 20% of engineering students with ADHD seek accommodations because they fear the stereotypes and stigma related to disability labels. Graduate students tend to rely even less on accessibility services than undergraduate students [21].…”
Section: Introductionmentioning
confidence: 99%